Na puti k nauchnoi teorii i metodologii sportivnoi trenirovki - Verchoshanskij, J. V. (Teorija i Praktika fiziceskoj Kul'tury, 1998)
The article contains the review of domestic and foreing literature, related to the theory and methodics of sports training, and specifically to the conception of so called "periodization" in a training process.